Wpływ systemu patentowego na dyfuzję wiedzy - Wachowska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
It is generally believed that the type of patent system of a country influences the range of knowledge diffusion in that country. It is usually thought that poor protection of intellectual property rights promotes diffusion of knowledge, although not that of fundamental discoveries, while strong protection of intellectual property rights promotes invention but it reduces diffusion of know-how. This hypothesis is confirmed by the results of few empirical studies. However, there are alternative opinions maintaining that in the long term it is the patent system that strongly protects rights of the inventor,which is more effective in knowledge diffusion.
Keywords: system patentowy; patenty; Japonia; Stany Zjednoczone Ameryki; wiedza